Konsep Doa Puja Yesus menurut Kallistos Ware: Doa Keheningan Batin (nepsis) - Wijaya, Rahmat; Indrawan , Yayan (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2024)
Prayer is one of the means that humans use to unite with God, and prayer is a human relationship with God, which brings humans to meet God in the prayers that come out of our mouths. Jesus’ prayer is a prayer that is alive and that heals human souls and minds, or that has an impact on people who believe in Him. The purpose of this research is to provide an impact on other people about prayer that lives and grows in human life, and why this prayer is called a living prayer that provides healing for the soul and mind of believers based on the book written by Kallistos Ware from Diokleia. The method used by the author in this research is qualitative. The author collects and writes from sources, such as books, journal articles, and from church fathers, which are related to this research. The findings in this paper explain that the Jesus prayer can be done anywhere or in your daily routine. This prayer can help humans in bringing their relationship closer to God, and will bring salvation from God, so that they will be like God.